Stability of organic solar cells with PCDTBT donor polymer: An interlaboratory study. Issue 13 (21st June 2018) - Ciammaruchi, Laura; Oliveira, Ricardo; Charas, Ana; Tulus,; von Hauff, Elizabeth; Polino, Giuseppina; Brunetti, Francesca; Hansson, Rickard; Moons, Ellen; Krassas, Miron; Kakavelakis, George; Kymakis, Emmanuel; et al.
Abstract: Abstract : This work is part of the interlaboratory collaboration to study the stability of organic solar cells containing PCDTBT polymer as a donor material. The varieties of the OPV devices with different device architectures, electrode materials, encapsulation, and device dimensions were prepared by seven research laboratories. Sets of identical devices were aged according to four different protocols: shelf lifetime, laboratory weathering under simulated illumination at ambient temperature, laboratory weathering under simulated illumination, and elevated temperature (65 °C) and daylight outdoor weathering under sunlight. The results generated in this study allow us to outline several general conclusions related to PCDTBT-based bulk heterojunction (BHJ) solar cells. The results herein reported can be considered as practical guidance for the realization of stabilization approaches in BHJ solar cells containing PCDTBT.